High Incidence of Metabolically Active Brown Adipose Tissue in Healthy Adult Humans: Effects of Cold Exposure and Adiposity - SAITO, Masayuki; OKAMATSU-OGURA, Yuko; KAWAI, Yuko; TSUJISAKI, Masayuki; MATSUSHITA, Mami; WATANABE, Kumiko; YONESHIRO, Takeshi; NIO-KOBAYASHI, Junko; IWANAGA, Toshihiko; MIYAGAWA, Masao; KAMEYA, Toshimitsu; NAKADA, Kunihiro (Diabetes (New York, N.Y.), 2009)
The significant roles of brown adipose tissue (BAT) in the regulation of energy expenditure and adiposity are established in small rodents but have been controversial in humans. The objective is to examine the prevalence of metabolically active BAT in healthy adult humans and to clarify the effects of cold exposure and adiposity. In vivo 2-[(18)F]fluoro-2-deoxyglucose (FDG) uptake into adipose tissue was measured in 56 healthy volunteers (31 male and 25 female subjects) aged 23-65 years by positron emission tomography (PET) combined with X-ray computed tomography (CT). When exposed to cold (19 degrees C) for 2 h, 17 of 32 younger subjects (aged 23-35 years) and 2 of 24 elderly subjects (aged 38-65 years) showed a substantial FDG uptake into adipose tissue of the supraclavicular and paraspinal regions, whereas they showed no detectable uptake when kept warm (27 degrees C). Histological examinations confirmed the presence of brown adipocytes in these regions. The cold-activated FDG uptake was increased in winter compared with summer (P < 0.001) and was inversely related to BMI (P < 0.001) and total (P < 0.01) and visceral (P < 0.001) fat areas estimated from CT image at the umbilical level. Our findings, being against the conventional view, indicate the high incidence of metabolically active BAT in adult humans and suggest a role in the control of body temperature and adiposity.